State Capture Analysis : How to Quantitatively Analyze the Regulatory Abuse by Business-State Relationships - Fiebelkorn, Andreas (World Bank, Washington, DC, 2019)
Abundant qualitative evidence reveals how public and private actors abuse regulations to seek rents, impede reforms, and distort the economy. However, empirical evidence of such behavior, including its economic costs, remains limited. For that reason, the objective of this paper is to help practitioners who seek to quantitatively analyze state capture make better use of experience, methodologies, and potential data sources. Based on a comprehensive body of existing empirical studies, it provides guidance to analyze state capture and its impact on the economy. Chapter one discusses the concept of state capture and its relevance for economic development. Chapter two presents the main avenues of how policies have been captured and the empirical evidence of their implications. Chapter three provides an analytical framework for state capture analysis and discusses various applied approaches. The chapter is organized into three components required for the assessment: (i) evidence of political connectedness, which discusses data collection methods and methodologies of analyzing political connections; (ii) evidence of de jure and de facto mechanisms, through which firms receive policy favors; and (iii) firm-level indicators to measure performance differences between politically connected and nonconnected firms. Finally, two annexes provide a list of potential data sources and an extensive compilation of studies that have empirically examined state capture.